PRMT1 Promotes the Self‐renewal of Leukemia Stem Cells by Regulating Protein Synthesis - Min Zhou; Yi Huang; Ping Xu; Shuyi Li; Chen Duan; Xiaoying Lin; Shilai Bao; Waiyi Zou; Jingxuan Pan; Chang Liu; Yanli Jin (Advanced Science)
Abstract The application of tyrosine kinase inhibitors (TKIs) has revolutionized the management of chronic myeloid leukemia (CML). However, disease relapse and progression particularly due to persistent leukemia stem cells (LSCs) remain a big challenge in the clinic. Therefore, validation of the therapeutic vulnerability in LSCs is urgently needed. This study verifies the critical role of protein arginine methyltransferase 1 (PRMT1) in the maintenance of CML LSCs. It is found that PRMT1 promotes the survival and serially plating abilities of human primary CML LSCs. Genetic deletion of Prmt1 significantly delays the leukemogenesis and impairs the self‐renewal of LSCs in BCR‐ABL–driven CML mice. PRMT1 regulates LSCs and leukemia development depending on its methyltransferase activity. Pharmacological inhibition of PRMT1 activity by MS023 remarkably eliminates LSCs and prolongs the survival of CML mice. Mechanistical studies reveal that PRMT1 promotes transcriptional activation of ribosomal protein L29 (RPL29) via catalyzing asymmetric dimethylation of histone H4R3 (H4R3me2a) at its gene promoter region. PRMT1 augments the global protein synthesis via RPL29 in CML LSCs. Taken together, the findings provide new evidence that histone arginine methylation modification regulates protein synthesis in LSCs and highlight PRMT1 as a valuable druggable target for patients with CML.